Translation initiation of viral mRNAs - López‐Lastra, Marcelo (Rev Med Virol, 2010)
Viruses depend on cells for their replication but have evolved mechanisms to achieve this in an efficient and, in some instances, a cell‐type‐specific manner. The expression of viral proteins is frequently subject to translational control. The dominant target of such control is the initiation step of protein synthesis. Indeed, during the early stages of infection, viral mRNAs must compete with their host counterparts for the protein synthetic machinery, especially for the limited pool of eukaryotic translation initiation factors (eIFs) that mediate the recruitment of ribosomes to both viral and cellular mRNAs. To circumvent this competition viruses use diverse strategies so that ribosomes can be recruited selectively to viral mRNAs. In this review we focus on the initiation of protein synthesis and outline some of the strategies used by viruses to ensure efficient translation initiation of their mRNAs. Copyright © 2010 John Wiley & Sons, Ltd.